2014
DOI: 10.1098/rspb.2013.2081
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary origins of diadromy inferred from a time-calibrated phylogeny for Clupeiformes (herring and allies)

Abstract: One of the most remarkable types of migration found in animals is diadromy, a life-history behaviour in which individuals move between oceans and freshwater habitats for feeding and reproduction. Diadromous fishes include iconic species such as salmon, eels and shad, and have long fascinated biologists because they undergo extraordinary physiological and behavioural modifications to survive in very different habitats. However, the evolutionary origins of diadromy remain poorly understood. Here, we examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
86
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 52 publications
(77 reference statements)
9
86
3
1
Order By: Relevance
“…Monophyly of the genus Alosa has been repeatedly supported based on mitochondrial, nuclear and combined molecular data (Bowen et al, ; Faria et al, ; Lavoué et al, ; Li & Orti, ); however, divergence times and rates of evolution have been a subject of debate (Bentzen et al, ; Bloom & Lovejoy, ; Faria et al, ; Lavoué et al, ). Our time‐calibrated analyses (Figure ) retrieved a topology identical to the composition of the major clades.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Monophyly of the genus Alosa has been repeatedly supported based on mitochondrial, nuclear and combined molecular data (Bowen et al, ; Faria et al, ; Lavoué et al, ; Li & Orti, ); however, divergence times and rates of evolution have been a subject of debate (Bentzen et al, ; Bloom & Lovejoy, ; Faria et al, ; Lavoué et al, ). Our time‐calibrated analyses (Figure ) retrieved a topology identical to the composition of the major clades.…”
Section: Discussionmentioning
confidence: 99%
“…Previous biogeographical studies that focused on large‐scale analyses of the clupeiforms suggested that the common ancestor of Alosa and Brevoortia might have originated in the western Atlantic Ocean, followed by subsequent eastward dispersal that established European groups of Alosa spp. (Bloom & Lovejoy, ; Lavoué et al, ). This hypothesis offers a parsimonious biogeographical scenario corroborated by the restricted present‐day distribution of Brevoortia on the Atlantic coast of the Americas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lycengraulis comprises one of these freshwater lineages, and is assumed to be a product of a marine incursion that occurred during the Miocene epoch in the paleo-environmental ecosystem known as the Pebasian Sea (which existed ,15 million years ago; Monsch 1998;Bloom and Lovejoy 2012). The Pebasian Sea was located in the area currently encompassing the Amazon basin, and consisted of brackish to freshwater salinities that drained north-migration has potential evolutionary consequences because the gene flow between migrants and residents tends to be reduced as a result of allopatric spawning (McDowall 2008;Chapman et al 2012;Bloom and Lovejoy 2014). Moreover, studies based on otolith chemistry (Mai et al 2014) have demonstrated the presence of a landlocked population of L. grossidens in the Parana Basin (Uruguay River; in areas as far as 1500 km from the sea).…”
Section: Introductionmentioning
confidence: 99%